2011
DOI: 10.1111/j.1526-4610.2011.02009.x
|View full text |Cite
|
Sign up to set email alerts
|

Migraine Attack Frequency, Duration, and Pain Intensity: Disease Burden Derived From a Community-Based Survey in Northern Tanzania

Abstract: To our knowledge, this study reports for the first time the burden that arises from migraine headache in a rural population of sub-Sahara Africa (SSA). As the presented migraine-related burden is considerable, we hope that our data will increase the awareness among local decision makers in allocating resources for treatment and research on headache.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Migraine is a disabling neurological disorder with substantial impact on personal health, work productivity, QOL and co-morbidity with other chronic diseases [ 2 ]. The findings of our study and those of others from sub-Saharan Africa re-iterate that migraine is not a mere inconvenience as it is often portrayed [ 4 - 12 ] and support the need for physicians and policy makers to take action to improve the quality of headache care and access to treatment in sub-Saharan Africa.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Migraine is a disabling neurological disorder with substantial impact on personal health, work productivity, QOL and co-morbidity with other chronic diseases [ 2 ]. The findings of our study and those of others from sub-Saharan Africa re-iterate that migraine is not a mere inconvenience as it is often portrayed [ 4 - 12 ] and support the need for physicians and policy makers to take action to improve the quality of headache care and access to treatment in sub-Saharan Africa.…”
Section: Discussionsupporting
confidence: 79%
“…In sub-Saharan Africa, where only five countries have contributed to primary headache disorder research, nine articles have been published in the span of almost ten years (1997–2006) [ 3 ]. In the past five years, there have been few studies investigating the burden of migraine [ 4 - 12 ] in accordance with International Classification of Headache Disorder (ICHD) criteria. A recent study conducted among Ethiopian adults found a migraine prevalence of 9.8% comparable to what is reported in occidental countries (10-15%) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Swartz et al 5 using the Epidemiology Catchment Area Follow-up Study reported a similar strong association between migraine and major depression (OR=3.1; 95% CI 2.0,4.8). Similarly, Breslau et al 10 in demonstrated that the prevalence of major depression was 3-times higher in persons with migraine compared to controls.…”
Section: Discussionmentioning
confidence: 85%
“…Globally, migraine is a major cause of disability 3 . Although there is a strong body of research on migraine and its impact on lost productivity costs in high income countries, the epidemiology of migraine in sub-Saharan Africa is not well documented 4, 5 . In the past two decades, very few studies have evaluated the burden of migraine in sub-Saharan Africa 6-10 using the International Classification of Headache Disorder (ICHD) criteria 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Of the 25 articles selected, all were subsequently rejected. Ten applied different definitions of headacheattributed disability and/or lost productivity, incompatible with ours [37][38][39][40][41][42][43][44][45][46]. Two did not measure both [47,48].…”
Section: Resultsmentioning
confidence: 99%